Lipoprotein particle concentration measured by nuclear magnetic resonance spectroscopy is associated with gestational age at delivery: a prospective cohort study. (16th October 2017) - Grace, MR; Vladutiu, CJ; Nethery, RC; Siega‐Riz, AM; Manuck, TA; Herring, AH; Savitz, D; Thorp, JT
Abstract : Objective: To estimate the association between lipoprotein particle concentrations in pregnancy and gestational age at delivery. Design: Prospective cohort study. Setting: The study was conducted in the USA at the University of North Carolina. Population: We assessed 715 women enrolled in the Pregnancy, Infection, and Nutrition study from 2001 to 2005. Methods: Fasting blood was collected at two time points (<20 and 24–29 weeks of gestation). Nuclear magnetic resonance (NMR) quantified lipoprotein particle concentrations [low‐density lipoprotein (LDL), high‐density lipoprotein (HDL), very‐low density lipoprotein (VLDL)] and 10 subclasses of lipoproteins. Concentrations were assessed as continuous measures, with the exception of medium HDL which was classified as any or no detectable level, given its distribution. Cox proportional hazards models estimated hazard ratios (HR) for gestational age at delivery adjusting for covariates. Main outcome measures: Gestational age at delivery, preterm birth (<37 weeks of gestation), and spontaneous preterm birth. Results: At <20 weeks of gestation, three lipoproteins were associated with later gestational ages at delivery [large LDLNMR (HR 0.78, 95% CI 0.64–0.96), total VLDLNMR (HR 0.77, 95% CI 0.61–0.98), and small VLDLNMR (HR 0.78, 95% CI 0.62–0.98], whereas large VLDLNMR (HR 1.19, 95% CI 1.01–1.41) was associated with a greater hazard of earlier delivery. At 24–28 weeks of gestation, average VLDLNMR (HR 1.25, 95% CI 1.03–1.51) and a detectable level of medium HDLNMR (HR 1.90, 95% CI 1.19–3.02) were associated with earlier gestational ages at delivery. Conclusion: In this sample of pregnant women, particle concentrations of VLDLNMR, LDLNMR, IDLNMR, and HDLNMR were each independently associated with gestational age at delivery for all deliveries or spontaneous deliveries <37 weeks of gestation. These findings may help formulate hypotheses for future studies of the complex relationship between maternal lipoproteins and preterm birth. Tweetable abstract: Nuclear magnetic resonance spectroscopy may identify lipoprotein particles associated with preterm delivery. Tweetable abstract: Nuclear magnetic resonance spectroscopy may identify lipoprotein particles associated with preterm delivery.